Changes in Intestinal Fluid Transport and Immune Responses to Enterotoxins Due to Concomitant Parasitic Infection - Ljungström, Inger (1980)
The effect of a parasitic infection on enterotoxic diarrhea and on local and systemic formation of antibody to the toxin after immunization was studied in mice. Trichinella spiralis infection was chosen as the model, since the effects of the parasite when residing in both intestinal and extraintestinal sites can be studied. It was found that during the intestinal stage of the infection, the fluid response to cholera toxin as well as dibutyryl-cyclic adenosine 3′,5′ -monophosphate was greatly enhanced and that this was associated with a marked reduction in the absorption of fluid from the intestine. Later in the infection (migration stage), fluid accumulation in response to cholera toxin was significantly reduced, whereas absorption was normal and secretion in response to dibutyryl-cyclic adenosine 3′,5′-monophosphate was somewhat increased. Still later in the infection (muscular stage), the fluid-secretory response to cholera toxin was normal. There was a drastic depression of local formation of antitoxin of both immunoglobulin and immunoglobulin classes in mice given the first two of four oral immunizations with cholera toxin during the intestinal stage of T. spiralis infection. When the priming was given before or after the intestinal stage, the local antitoxin response was not affected. The titers of circulating antibodies were also depressed in mice given the first immunizations during the intestinal stage. In addition, significant though less pronounced depression of the serum antibody response was observed in mice primed during the extraintestinal stage.